2020
DOI: 10.1016/j.bbrep.2019.100715
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological evidence for the use of Cissus assamica as a medicinal plant in the management of pain and pyrexia

Abstract: The existing therapeutic agents for the management of pain and pyrexia are not very efficient and accompanied by numerous side effects. Thus, new effective agents are the most needed. The present study investigates bioactivities and phytochemical screening of different parts of Cissus assamica (Vitaceae), a Bangladeshi tribal medicinal plant. Three plant parts stems, leaves and roots were collected, washed, dried, powdered and then prepared for cold extraction. The methanolic stems and leaves extracts were fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 30 publications
0
32
0
Order By: Relevance
“…This reduction of temperature was observed might be due to the presence of some pharmacologically active constituents in A. auriculiformis, which interfere with the synthesis of prostaglandin. However, phytochemicals, specifically steroids and flavonoids, are known as a good antipyretic agent and in the previous study presence of these phytochemicals has been observed in A. auriculiformis [13,48]. Nevertheless, it must be noted that diverse biochemical reactions take place during the synthesis of prostaglandins.…”
Section: Discussionmentioning
confidence: 88%
“…This reduction of temperature was observed might be due to the presence of some pharmacologically active constituents in A. auriculiformis, which interfere with the synthesis of prostaglandin. However, phytochemicals, specifically steroids and flavonoids, are known as a good antipyretic agent and in the previous study presence of these phytochemicals has been observed in A. auriculiformis [13,48]. Nevertheless, it must be noted that diverse biochemical reactions take place during the synthesis of prostaglandins.…”
Section: Discussionmentioning
confidence: 88%
“…In addition, the products used in traditional medicine are processed in various forms, such as powder, extracts, capsules, and tablets. Phytochemical characterization could therefore be used in the identification and authentication of several medicinal plants [ 20 , 21 , 22 , 23 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, organic acid is also thought to function indirectly to trigger the release of endogenous mediators that activate nociception [49,50]. It is notable that NSAIDs and pain-relieving drugs act by preventing moderate degrees of pain with the formation of antinociceptive signals that block the synthesis of prostaglandins, tumor necrosis factor-α, and bradykinin [51]. During the writhing test, MEAM and the standard drug diclofenac sodium showed a significant (p < 0.001) and dose-dependent number of writhing events as compared with in the control group.…”
Section: Discussionmentioning
confidence: 99%